Pengaruh kompetisi, ukuran bank (size), produk domestik bruto pdb) dan inflasi terhadap rasio modal pada perbankan indonesia periode tahun 2011-2015 - Nadia Azmi Hafidhoh; Justina Ade Judiarni; Rizky Yudaruddin (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2018)
This study aimed to examine the effect of competition, size of the Bank, GDP and Inflation to Capital Ratio. Competition is measured using a model of the H-Statistics Panzar and Rosse (1987), the bank size log n measured by total assets of the bank, as well as GDP and inflation as measured by annual growth. With samples on National Private Banks (BUSN) Foreign exchange registered in Bank Indonesia in the 2011-2015 period amounted to 38 banks. By using data analysis tools Eviews version 8. The results showed that competition is not significant negative effect on capital ratios, the size of the bank and inflation gave a significant negative impact, and GDP growth is not significant positive effect on capital ratios.